2015
DOI: 10.1073/pnas.1506825112
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic collective effects of active protein machines in solution and lipid bilayers

Abstract: The cytoplasm and biomembranes in biological cells contain large numbers of proteins that cyclically change their shapes. They are molecular machines that can function as molecular motors or carry out various other tasks in the cell. Many enzymes also undergo conformational changes within their turnover cycles. We analyze the advection effects that nonthermal fluctuating hydrodynamic flows induced by active proteins have on other passive molecules in solution or membranes. We show that the diffusion constants … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
113
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(129 citation statements)
references
References 46 publications
7
113
0
5
Order By: Relevance
“…As solute particles move, they induce a flow in the solvent, which, in turn, affects the motion of neighboring solute particles. These long-range interactions between solute particles through solvent, known as hydrodynamic interactions (HI), have been shown to play an essential role in protein dynamics [24]. HI is studied extensively in polymers both analytically [5,6] and numerically [7].…”
Section: Introductionmentioning
confidence: 99%
“…As solute particles move, they induce a flow in the solvent, which, in turn, affects the motion of neighboring solute particles. These long-range interactions between solute particles through solvent, known as hydrodynamic interactions (HI), have been shown to play an essential role in protein dynamics [24]. HI is studied extensively in polymers both analytically [5,6] and numerically [7].…”
Section: Introductionmentioning
confidence: 99%
“…It was proposed that the observed diffusion enhancement of the tracers was due to the momentum transferred from the active enzymes to their neighborhood following one of the several proposed mechanisms.A ccording to Mikhailov and Kapral, active enzymes act as stochastic oscillating force dipoles that generate hydrodynamic flows and thereby collectively affect the diffusion of passive tracers. [205,206] As imilar proposition was put forward by Yasuda et al when discussing the diffusive motion of tracers in viscoelastic active media. [207] Mikhailov et al provided estimates of such hydrodynamic coupling at enzyme concentrations of the order of 10 À6 m,keeping in mind the typical concentration of active proteins inside cells.T heir calculations,h owever,c an also be used to predict such an effect at lower enzyme concentrations (nm), provided the enzymes are considered to be generating intramolecular forces that give rise to hydrodynamic force dipoles.T he experimental studies with enzymes,t herefore,m ight have involved the generation of such strong forces-leading to the enhanced diffusion of the tracers.T he incorporation of the rotational diffusion of enzymes into these models [205,206,208] was found to modify the estimates slightly,without obscuring the principal effects.C omplete orientational fluctuations of particles were further explicitly taken into consideration by Dennison et al in their multiparticle simulations.…”
Section: Nanoscale-and Ngstrçm-scale Systemsmentioning
confidence: 88%
“…[205,206] As imilar proposition was put forward by Yasuda et al when discussing the diffusive motion of tracers in viscoelastic active media. [207] Mikhailov et al provided estimates of such hydrodynamic coupling at enzyme concentrations of the order of 10 À6 m,keeping in mind the typical concentration of active proteins inside cells.T heir calculations,h owever,c an also be used to predict such an effect at lower enzyme concentrations (nm), provided the enzymes are considered to be generating intramolecular forces that give rise to hydrodynamic force dipoles.T he experimental studies with enzymes,t herefore,m ight have involved the generation of such strong forces-leading to the enhanced diffusion of the tracers.T he incorporation of the rotational diffusion of enzymes into these models [205,206,208] was found to modify the estimates slightly,without obscuring the principal effects.C omplete orientational fluctuations of particles were further explicitly taken into consideration by Dennison et al in their multiparticle simulations. [209] Their results were also in good agreement with the original theoretical predictions.Infact, the increase in tracer diffusion correlated inversely with tracer size (1/R)i ne xperiments, similar to the observations made with active microscopic systems.…”
Section: Nanoscale-and Ngstrçm-scale Systemsmentioning
confidence: 88%
“…Hydrodynamic interactions are therefore key to understanding both the motion of proteins in dilute and in crowding conditions. This has been pointed out in seminal theoretical and experimental work [7][8][9][10].…”
Section: Introductionmentioning
confidence: 86%
“…In a recent work [49] reporting on the effect of hydrodynamics on the aggregation process of Aβ 16−22 peptides in systems of different sizes, we have demonstrated that hydrodynamic interactions not only speed up the aggregation with respect to standard Langevin dynamics, but also enhance the fluctuations of the sizes of the formed clusters along the aggregation. It was speculated that the peptides aggregates act on the solution as active particles [9], and the change of their conformations and sizes generate coherent fluid flows that further favour the fusion of small entities in larger complexes.…”
Section: (B) Amyloidsmentioning
confidence: 99%